2014
DOI: 10.1371/journal.pone.0093673
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions in Brain Networks of Older Fallers Are Associated with Subsequent Cognitive Decline: A 12-Month Prospective Exploratory Study

Abstract: Cognitive impairment and impaired mobility are major public health concerns. There is growing recognition that impaired mobility is an early biomarker of cognitive impairment and dementia. The neural basis for this association is currently unclear. We propose disrupted functional connectivity as a potential mechanism. In this 12-month prospective exploratory study, we compared functional connectivity of four brain networks– the default mode network (DMN), fronto-executive network (FEN), fronto-parietal network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 91 publications
1
33
0
Order By: Relevance
“…The articles are from 15 different countries, but especially from the United States of America (18)(19)(24)(25)30,33,39,(53)(54)(55)(56)(57)(58)(59)(60)(61) and Australia (17,28,32,34,36,42,44,(46)(47)52,(62)(63)(64) , with 16 and 13 studies, respectively. The other countries with most articles were Canada (23,29,40,(65)(66)(67)(68) with seven, Netherlands (20,31,35,51,69) with five, and United Kingdom (48,(70)(71)(72) with four. Then came China (26,50,73) , France (45,49,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles are from 15 different countries, but especially from the United States of America (18)(19)(24)(25)30,33,39,(53)(54)(55)(56)(57)(58)(59)(60)(61) and Australia (17,28,32,34,36,42,44,(46)(47)52,(62)(63)(64) , with 16 and 13 studies, respectively. The other countries with most articles were Canada (23,29,40,(65)(66)(67)(68) with seven, Netherlands (20,31,35,51,69) with five, and United Kingdom (48,(70)(71)(72) with four. Then came China (26,50,73) , France (45,49,…”
Section: Resultsmentioning
confidence: 99%
“…Age ≥ 65 years (50,61,63,73,74,77) 6 √ History of falls (28,50,53,57,63,67,69) 7 √ Living alone (63) 1 √ Lower limb prosthesis 0 √ Use of assistive devices (e.g. walker, cane, wheelchair) (17,41) 2 √ Female (20,38,40,59,63,73,74,77) 8…”
Section: Risk Factors N Nanda-i Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of brain function, our own work demonstrated that compared with their non-faller counterparts, older adults with a history of multiple falls (i.e., ≥ 2 non-syncope falls in the previous 12 months) showed aberrant neural network functional connectivity -a measure of synchronous brain activity (Hsu et al 2014). Notably, the aberrant network connectivity demonstrated by fallers was independently associated with greater decline in both executive functions and mobility over a 12-month period after accounting for relevant covariates (Hsu et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Consistent with these links between mobility and cognition, evidence from neuroimaging studies suggests that slower gait speed or a history of falls is associated with subclinical alterations in both brain structure and function (Rosano et al 2008;Hsu et al 2014;. With respect to structure, in a cross-sectional study of 220 community-dwelling older adults, Rosano and colleagues (Rosano et al 2008) demonstrated that lower gray matter volume in the sensorimotor regions and frontoparietal regions were associated with impaired gait (i.e., shorter steps and longer double support times).…”
Section: Introductionmentioning
confidence: 94%